La Misión del Tíbet en Nueva España: las limosnas y el cobro del legado de Spinola - Lorenzen, David N. (El Colegio de México, A.C., 2013)
In 1736, the King of Spain declared that the responsibility of paying a debt of almost 135,000 silver pesos, the so-called Spinola's legacy, owned by the Crown to the Congregation De Propaganda Fide in Rome, would fall on the government of New Spain. Propaganda argued that the money was allocated to the Tibet Mission, assigned to the Capuchin Order. The King also allowed some Capuchins to collect alms for this Mission in Mexico. During the next 50 years, Capuchins -especially the ambicious friar Fermín de Olite- negotiated the annual payments of  Spinola's legacy and the collection of alms for the Mission in Mexico. Even though they had to fight the government's resistance to part with the money, they finally succeeded on collecting the whole debt and a considerable quantity of alms.